Mismatch distribution of population and industry in China: Pattern, problems and driving factors. (August 2018) - Guan, Xingliang; Wei, Houkai; Lu, Shasha; Su, Hongjian
Abstract: The spatial agglomeration of population and industry is a worldwide economic phenomenon. Whether a country's population and industries be synergistically and matched agglomerated in space would significantly affect its socio-economic efficiency, coordinated regional development and even comprehensive competitiveness. Based on geographic information technology and multi-source data, this paper attempts to analyze the situation on the spatial distributed process of China's population and industry since the reform and opening-up and its resulting problems, investigate the driving factors, and finally examine the policy implications. The results indicate that population and industry agglomerated in the eastern region was an inevitably historical phenomenon during the urbanization process since economic reform in 1980s. The scale and speed of the spatial agglomeration of population and industry, however failed to be coordinated, resulting in a series of prominent problems including i) migration of hundreds of millions of "amphibious migratory" type peasant workers, ii) cross-regional conveying of energy and bulk commodities, iii) tremendous pressure on resources and environment in the metropolitan areas, and iv) increasingly intensified unstable factors and social contradictions. The reason for the phenomenon and problems might be attributed to i) regional differences in natural conditions and resources endowment of the country, ii) eastern-oriented national development strategy, iii) spatial agglomeration effect and scale effect of resources and elements, iv) obvious development and income gaps between the eastern and the inner regions, v) strict urban-rural dual household registration system, and vi) increasingly high cost of housing and livelihood of the urbanization area. The essence to establish an efficient, balanced and safe spatial pattern of urbanization is to realize an intra- and inter-regional harmonious development across the country. The study emphasizes that the Chinese government should devote itself to implementing suitable development policies to not only enhance people's prosperity, but also highlight the region's prosperity. Several alternative solutions and measures are also discussed, which may be helpful for the country to optimize the spatial layout of urbanization. Highlights: The spatial agglomeration of population and industry is a worldwide economic phenomenon. The scale and speed of spatial agglomeration of population and industry in China failed to be coordinated. The Chinese government should implement policies to enhance people's prosperity and highlight the region's prosperity.